Inverted Reality in Nabokov's Look at the Harlequins! - D. Barton Johnson (Studies in 20th & 21st Century Literature, 1984)
Look at the Harlequins! presents itself as the autobiography of a famed Anglo-Russian writer who suffers from bouts of insanity that are connected with his feeling that he is the inferior copy of another, much better writer. The autobiography is devoted mainly to his four great loves and to his books. Close analysis suggests that the narrator's account is false and is essentially a record of his delusive life during periods of insanity. LATH is seen as an example of those of Nabokov's novels that have schizoid narrators, such as The Eye, Despair, and Pale Fire, and is set in opposition to another group of novels (Invitation to a Beheqding, Bend Sinister, and Ada) in which the fictional worlds themselves are twinned.
Keywords: Look at the Harlequins; Nabokov; insanity; schizophrenia; autobiography; schizoid narrators; The Eye; Despair; Pale Fire; Invitation to a Beheqding; Bend Sinister; Ada; inverted reality